2012
DOI: 10.1136/emermed-2012-201581
|View full text |Cite
|
Sign up to set email alerts
|

Haemostatic dressings in prehospital care

Abstract: Massive haemorrhage still accounts for up to 40% of mortality after traumatic injury. The importance of limiting blood loss after injury in order to prevent its associated complications has led to rapid advances in the development of dressings for haemostatic control. Driven by recent military conflicts, there is increasing evidence to support their role in the civilian prehospital care environment. This review aims to summarise the key characteristics of the haemostatic dressings currently available on the ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
65
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(65 citation statements)
references
References 38 publications
0
65
0
Order By: Relevance
“…[6,8,9] Although very successful in achieving bleeding control, smectite is outdated because of its potential for tissue damage and inability to wipe it off the tissue. [15,27] Chitosan seems relatively safe; the only concern regarding its use may be shellfish allergy of the individual. [14,15] Kaolin is also safe but needs more time for achieving hemostasis and an intact coagulation system in the individual.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[6,8,9] Although very successful in achieving bleeding control, smectite is outdated because of its potential for tissue damage and inability to wipe it off the tissue. [15,27] Chitosan seems relatively safe; the only concern regarding its use may be shellfish allergy of the individual. [14,15] Kaolin is also safe but needs more time for achieving hemostasis and an intact coagulation system in the individual.…”
Section: Discussionmentioning
confidence: 99%
“…[15,27] Chitosan seems relatively safe; the only concern regarding its use may be shellfish allergy of the individual. [14,15] Kaolin is also safe but needs more time for achieving hemostasis and an intact coagulation system in the individual. [8] Dry fibrin sealants are expensive and fragile for battlefield environment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, kaolin activates the XII factor of the coagulation cascade 19 and is dependent upon an adequately functioning coagulation cascade. 20 However, small, ongoing animal research studies have demonstrated QuikClot's effi cacy with both hypothermia and dilutional coagulopathy. 21,22 Because of its mechanism of action, QuikClot may not provide immediate hemostasis and may cause more initial blood loss.…”
Section: Hemostatic Dressingsmentioning
confidence: 99%
“…As well as efficacy and safety, these include ease of administration and stability of the product. There is a growing body of literature which describe the relative merits and disadvantages of products such as QuikClot Ò Combat Gauze (a Zeolite mineral based compound), WoundStat Ò (a granular combination of a smectite mineral and a polymer), Celox Ò (a chitosan product) and HemCon Ò (a complex polysaccharide-chitosan) as adjuncts to pressure control in peripheral injuries (reviewed in detail by Granville-Chapman et al [8] and Smith et al [9]). However, these products are primarily for external application and may not be licensed for intra-cavity use.…”
Section: Local Haemostatic Agentsmentioning
confidence: 99%